The Development of the Potential of Learning An Interview with Reuven Feuerstein - Sergio Noguez Casados (Universidad Autónoma de Baja California, 2012)
Dr Reuven Feurstein's answers to this interview provide a first approximation to the work he has been doing for the last 40 years. It belongs to the area of structural cognitive psychology, with an interesting new use of the typical tools of psychometry focused on the development of thinking skills, not on IQ testing. Dr. Feuerstein offers a current balance of the most important fields he has been working on, which can be applied to different educational settings, from preschool to the training of High-Tech pilots.